Urban farming for community well-being in Klang Valley, Malaysia - Zainal, Milah; Hamzah, Siti Raba'ah; Krauss, Steven Eric; Tengku Muda, Tengku Mahmud (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
By 2030, 60-85% of human beings will be living in urban areas. Increasing human populations are causing social, environmental, economic and political problems worldwide and well-being benefits. Urban farming (UF) is one approach for sustainable development that has the potential to provide food within or on the edges of urban areas. UF has gained popularity in cities all over the world and one of the approaches used is through community farming. Community farming are green spaces that practiced on public land with the full authority of the local authorities that provide food, community, and economic benefits. Thus, investigating their significance and benefit across urban regions is critical for research and policy alike. This study explores the contribution of community farming in providing economic well-being of the urban farmers in the Klang Valley, Malaysia. A qualitative approach, via in-depth interviews and observations was used to collect detailed information from eight informants. Data were analyzed and coded to categories and sub-themes. The findings revealed that urban farmers perceived that community farming enhance their economic well-being by reduce cost of living, household food insecurity, create job opportunities and generate income. Community farming is lauded as an urban planning tool to enhance local food systems while improving degraded urban economic. Community farming are therefore important for supporting many well-being benefits. However, since urban agriculture is profitable, more urban farmers should be encouraged to engage in this activity.